Crime Prevention Practice Paper 1: An Overview of CPTED DCPs and Related Council Policies in NSW - Chiu, Dave Yue Kim (2011)
Crime prevention through environmental design (CPTED) is increasingly adopted by councils across New South Wales (NSW). This can be done in a variety of ways. Introducing Development Control Plans (DCPs) focusing on CPTED or integrating CPTED into larger DCPs are two key ways that this has been achieved. This Crime Prevention Practice Paper provides an overview of some of the methods used by councils to embed CPTED into local planning regimes and provides examples of documents developed by various NSW councils